IPTEKS SISTEM AKUNTANSI INSTANSI BERBASIS AKRUAL (SAIBA) DALAM PENYAJIAN LAPORAN KEUANGAN PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN PROVINSI SULAWESI UTARA - Tampemawa, Patrycia Marcellina Maria; Kindangen, Wulan D (Universitas Sam Ratulangi, 2018)
The institute of Educational Quality Assurance is a government agency engaged in education, which aims to ensure that standards, norms, criteria and procedures set by the central government in accordance with the implementation of education in North Sulawesi. In this agency all the parts that have to be able to run well to realize good governance, one of whichÂ the finance department whose job is to present financial statements. The application of accrual-based accounting in the central or regional government is supported by the existence of the SAIBA application, so that the presentation of financial statements, one of which is the financial report at LPMP, assisted by the application of SAIBA. Referring to PMK 270 / PMK.05 /2014 wherein it has been equipped with an Operational Report, Equity Change Report, where in the previous system only issued two types of reports, that is Budget Realization Report and Report form Balance Sheet. The financial statements must be appended with theÂ Financial Statement notes for annual report. Keyword: Financial statements, Accrual Basis, SAIBA